Diversity Networks: Networking for Equality?. (31st July 2018) - Dennissen, Marjolein; Benschop, Yvonne; van den Brink, Marieke
Abstract: In recent years, the use of diversity networks as diversity management instruments in organizations has increased tremendously. Diversity networks support the needs of employees with different social identities, such as women, ethnic minorities, LGBTs, disabled and young people. The aim of this study is to come to a better understanding of how diversity networks contribute to equality by examining how diversity network leaders discursively construct the value of their networks against the backdrop of discourses on diversity and equality. We conducted a multiple case study of five different diversity networks in a financial service organization in the Netherlands. Our results show that network leaders tend to construct the value of their networks primarily in terms of individual career development and community building, to prevent their members' isolation. However, they are much less articulate about removing the barriers to inclusion in the organization as a core value of their networks. We conclude that the value of diversity networks is limited when these networks only address the individual and group levels of equality and leave systemic inequalities at the organizational level unchallenged.